Role of human brain microvascular endothelial cells during central nervous system infection - Adam, Rüdiger; Rüssing, Daniel; Adams, Ortwin; Ailyati, Aziz; Kim, Kwang Sik; Schroten, Horst; Däubener, Walter (Thrombosis and Haemostasis, 2005)
The cerebral endothelium is involved both in regulatinthinflux g e of immune cells into the brain and in modifying immunological reactions within the CNS. A number of human pathogens may cause encephalitis or meningitis when this important protective barrier is impaired. We have previously shown that interferon- γ activated human brain microvascular endothelial cells (HBMEC) restrict the growth of bacteria and parasites. We now provide evidence that HBMEC are also capable of inhibiting viral replication after stimulation with IFN-γ, an effect further augmented by costimulation with IL-1. This antiviral effect was completely blocked in the presence of L-tryptophan, indicating the induction of the tryptophan degrading enzyme indoleamine 2,3-dioxygenase (IDO) to be responsible for the observed antiviral effect. Apart from exerting antimicrobial effects tryptophan depletetion has also been described as a regulatory mechanism in T cell responses to both allo- and autoantigens. We were able to demonstrate that IDO mediated degradation of L-tryptohan in HBMEC is responsible for a significant reduction inT lymphocyte proliferation. Resupplementation of L-tryptophan and restoration of initial T cell responses demonstrated the central role of this essential amino acid in the reduction of T-cell proliferation. Brain endothelial cells appear to limit microbial expansion in the CNS by local degradation of tryptophan, thus acting in concert with other IDO-positive cell populations on the parenchymal side of the blood-brain barrier such as astrocytes, microglia and neurons. Since all dietary tryptophan must cross the blood-brain barrier, the microvascular endothelial cells may play a key role in restricting tryptophan influx from the bloodstream into the brain. As deleterious effects of brain infections can often be attributed to subsequently invading immune cells, an IDO-mediated reduction of lymphocyte proliferation may be beneficial for preventing collateral brain damage.
Keywords: Meningitis; encephalitis; IDO; kynurenine; herpes simplex virus